IMPLEMENTATION OF FINITE VOLUME METHOD FOR BACTERIAL TRANSPORT PROBLEM IN POROUS MEDIA - PUJI HARSAGI (NIM : 10109096); pembimbing : Dr. Agus Yodi Gunawan, SOLPA
Bacterial transport in porous medium may be represented into a mathematical model. The terms that are involved in the model can be classified into advection, diffusion, and external forces describing the interaction between the bacterial and its environment. In this final project, the model will be solved numerically by using The Finite Volume Method. The core of the method is the integration of differential equation which is derived from the Conservation Law into algebraic equation. The method also confines the regions of numerical solutions which is called Control Volume. Here, two discretization methods, explicit and implicit methods, will be implemented.